If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4m + -1 = 5 Reorder the terms: -1 + 4m = 5 Solving -1 + 4m = 5 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 4m = 5 + 1 Combine like terms: -1 + 1 = 0 0 + 4m = 5 + 1 4m = 5 + 1 Combine like terms: 5 + 1 = 6 4m = 6 Divide each side by '4'. m = 1.5 Simplifying m = 1.5
| 3p^2+22p-16=0 | | -1.6(x-18)+1.3(x+3)=x+34 | | -x^2+12x+28=0 | | -1.6(x-18)+0.5(x+3)=x-8 | | 11x+8=4x-27 | | x+3/2*8=x/8 | | 4+3a=4(a+2) | | 5b^2-22b+8=0 | | 4z^2+12z-az-3a= | | 6+4n=2 | | T^2+23t+90=0 | | 2b^2+5b-12=0 | | 4=x+14 | | 12b^2-7b+1=0 | | 4=x+10 | | x-18=3x | | 4(x+2y)= | | n-8(1+n)=-4n-32 | | -3y+12=-2(3y+6) | | 4x+3=c | | 5((-8-3y)-2)-2y=-1 | | n-8(1+n)=-4-32 | | y=6x-x^2-8 | | 3b^2-16b+5=0 | | 2x^3+14x^2+24x= | | 2b^2-b-10=0 | | -(y+12)=4 | | 21-5=4 | | 0.8x+4=12 | | -9(t-4)-(t+5)=3 | | 3b^2-13b+4=0 | | 3x^6y^4+27x^4y^3+15xy= |